1989
DOI: 10.1017/s0021859600070106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acidification with sulphuric acid on the volatilization of ammonia from cow and pig slurries

Abstract: SUMMARYPig and cow slurries were applied to bare soil surfaces in the laboratory. Volatilization of NH3 was measured using ventilated enclosures for 3·25 days after slurry application. Slurries were acidified to pH values between 7 and 4 with 5 M H2SO4. Lowering cow slurry pH to 5·5 decreased NH2 volatilization by 95%, while lowering pig slurry pH to 6·0 decreased NH3 volatilization by 82%. A field experiment, measuring the volatilization of NH3 for 2 h after application to grassland stubble of slurry acidifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 13 publications
5
57
0
Order By: Relevance
“…The technologies applied in a specific country depends on several factors such as local policies, livestock numbers, population density, climate and amount of arable land in need of fertilization. Well-established methods in practical use include the acidification of manure slurry in livestock housing or in storage tanks before application to the field (Stevens et al 1989) and physical barriers, such as closed or covered storage tanks (Funk et al 2004;Scotford and Williams 2001). These methods rely on either physically trapping the formed NH 3 or converting volatile NH 3 to non-volatile NH 4 ?…”
Section: Established Technologies For Ammonia Emission Mitigation In mentioning
confidence: 99%
See 1 more Smart Citation
“…The technologies applied in a specific country depends on several factors such as local policies, livestock numbers, population density, climate and amount of arable land in need of fertilization. Well-established methods in practical use include the acidification of manure slurry in livestock housing or in storage tanks before application to the field (Stevens et al 1989) and physical barriers, such as closed or covered storage tanks (Funk et al 2004;Scotford and Williams 2001). These methods rely on either physically trapping the formed NH 3 or converting volatile NH 3 to non-volatile NH 4 ?…”
Section: Established Technologies For Ammonia Emission Mitigation In mentioning
confidence: 99%
“…Furthermore, acidification helps limit ammonia volatilization after the application of the manure slurry fertilizer to the field (Kai et al 2008;ten Hoeve et al 2016). Previous studies found a reduction in ammonia volatilization from the fields of up to 95% when the pH of the manure slurry was lowered to 5.5 with sulfuric acid (Stevens et al 1989). As an alternative to acidifying the manure slurry directly, chemical filters have been developed.…”
Section: Established Technologies For Ammonia Emission Mitigation In mentioning
confidence: 99%
“…Researchers have shown reduced NH 3 emissions when manure slurry pH was lowered (Husted et al 1991;Stevens et al 1989). Recently, a lignite coal extract (LC, SHAC ® Environmental Products Inc.) has been reported to reduce the release of odourous compounds from liquid lagoons when included in the diets of swine (Bundy and Zhu 1995;Zhu et al 1997a, b).The LC consists mainly of humic acids derived from soluble lignite coal that arise as a result of the decomposition of plant material.…”
Section: Mots Clésmentioning
confidence: 99%
“…Reduction of gaseous emissions from livestock manure has been shown to be possible, particularly with acidifying and adsorbent additives (Stevens et al 1989;Frost et al 1990), and the potential exists to develop practical and costeffective control technologies. For example, incorporation of bedding materials with manure has been proposed for reducing gaseous emissions (Mahimairaja et al 1994).…”
Section: Introductionmentioning
confidence: 99%